Análisis sintáctico-semántico del verbo ganar según el enfoque orientado a objetos - Palion-Musioł, Agnieszka; Żłobińska-Nowak, Aleksandra (Neophilologica, 2014)
The article discusses the natural polysemy of the lexicon of natural languages, perceived as one of the major problems of automatic translation. It also presents a solution for the problem of disambiguation of ambiguous expressions — it pivots on the object-oriented description, enriched with a transfer of various possible translations in a target language taking into consideration possible ambiguity in a source language. Finally, the authors show differences in the representations of the world in Polish and Spanish, using the example of some Polish renderings of the Spanish verb ganar.